LEADERSHIP OF THE SCHOOL PRINCIPLE IN THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS CREATIVE SCHOOLS MTs - Billa, Mohammad Zainul Arifin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to reveal the type of school leadership, creative efforts in developing creative and superior educational institutions, with sub-focuses including: (1) What type of leadership is applied by the principal in the development of MTs Mikhrajul Ulum Creative Islamic educational institutions, (2) what efforts are made by the principal in developing MTs Mikhrajul Ulum Creative Islamic educational institutions, and (3) the desired output of MTs Mikhrajul Ulum Kreatif targets. This research uses qualitative research in the form of case studies. Data collection is done by interviews, observation, and documentation. While data analysis techniques, researchers use interactive models that contain four related components, namely: data collection, data simplification, data exposure, and conclusion drawing and archiving. The results showed that: (1) the type of principal who applies MTs Mikhrajul Ulum's creative leadership, namely democratic leadership (aspirational, accommodating, assertive and open), where the principal during the lead is able to make changes and has a vision for the future. Islamic educational institutions to develop MTs Mikhrajul Ulum Kreatif towards creative and superior schools; (2) what efforts the principal made in the development of the Islamic educational institution MTs Mikhrajul Ulum Kreatif to build a school system; (3) how the desired output targets of MTs Mikhrajul Ulum are creative, which include: initial output (Preliminary Results) and general output targets.